Iconicity (of Reading). Lolita - Melnikova, Irina (Semiotika, 2021)
The paper focuses on the issue of iconicity of (printed) literary narrative and proposes the idea of iconic reading (or iconicity of reading). It discusses Peircean notion of iconic sign, examines its use within the field of iconicity studies in language and literature (Olga Fischer, Christina Ljungberg, Winfried Nöth, etc.), and considers the differences of paradigms in iconicity research: (1) iconicity as a permanent property of a sign; imitation pattern – form mimes meaning; (2) iconicity as a variable quality of a sign, actualized by the speaker; imitation pattern – form miming form; (3) iconicity as the ground of human thought and a function of a sign, actualized by the reader / reading. Consideration of the differences within the field of iconicity research helps to reveal the underestimated textual aspects that actualize iconic dimension of literary narrative, and inspires to examine their role in the analysis of Lolita by Vladimir Nabokov, precisely, its “Foreword” (both original English and Russian versions). The analysis of the fictional “Foreword”, which establishes the pattern of iconization of the novel as a whole, and inevitably includes the references to its “main” part, shows how the novel iconizes writing. Withal, the analysis demonstrates how this iconization configures the particular model of reading, which becomes the representamen of the specific cognitive icon. The mental representamen of this icon “stands for” the specific object – the text as the tangible media product, marked by the structural and discursive traits of its own. Respectively, such (cognitive) icon represents the pattern of mimetic relationship between form and meaning, introduced by Lars Elleström (2010), – meaning mimes form, worthy of further consideration.
Keywords: iconicity; indexicality; interpretant; Peirce; “Lolita”